Governance and responses of health and surveillance systems to COVID-19 in BRICS countries: A scoping review protocol. - Adelyne Maria Mendes Pereira; Monique Azevedo Esperidião; Sílvia Karla Azevedo Vieira Andrade; João Felipe Marques Silva; Louise Celeste Rolim Silva; Adriano Silva; Isabela Barboza da Silva Tavares Amaral; Isabel Domingos Martinez Dos Santos; Thalyta Cássia de Freitas Martins; Aline Degrave (PLoS ONE)
Registration This protocol is registered on the Open Science Framework (OSF) (available at https://doi.org/10.17605/OSF.IO/SN5ZY) and Figshare (available at https://doi.org/10.6084/m9.figshare.25908340) platforms.